Long non-coding RNA TINCR suppresses growth and epithelial-mesenchymal transition by inhibiting Wnt/β-catenin signaling pathway in human pancreatic cancer PANC-1 cells: Insights from in vitro and in vivo studies - Wei Yuan; Zhu Ping (Acta Pharmaceutica)
There is increasing evidence that long non-coding RNAs (lncRNAs) play a crucial role in the development and progression of malignant tumors, particularly pancreatic cancer. In this study, the influence of the lncRNA TINCR on the behavior of human pancreatic cancer cells was investigated with the aim of deciphering its role in growth, migration, and invasion. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to investigate TINCR expression in pancreatic cancer cells. Ectopic expression of TINCR in PANC-1 cells was induced to evaluate the effects on cell viability and apoptosis, examining the apoptotic genes Bax and Bcl-2. Migration and invasion assays were used to measure the impact of TINCR on these cellular processes. In vivo studies using a xenograft mouse model examined the effects of TINCR on tumor growth, epithelial-to-mesenchymal transition (EMT) markers, and the Wnt/β-catenin signaling pathway. PANC-1 cells showed strikingly low TINCR expression compared to other pancreatic cancer cell lines. Ectopic TINCR expression reduced the viability of PANC-1 cells primarily by inducing apoptosis, as evidenced by increased Bax and decreased Bcl-2 expression. Overexpression of TINCR significantly increased the percentage of apoptotic cells. It also decreased the migration and invasion ability of PANC-1 cells, as demonstrated in wound healing and transwell assays. In addition, overexpression of TINCR-suppressed proteins is associated with the Wnt/β-catenin signaling pathway in PANC-1 cells. In the xenograft mouse model, overexpression of TINCR inhibited tumor growth, EMT markers, and proteins associated with the Wnt/β-catenin pathway. This study sheds light on the tumour-suppressive role of TINCR in PANC-1 cells and suggests its potential as a therapeutic target. These results shed light on the molecular mechanisms underlying the impact of TINCR on pancreatic cancer and offer promising opportunities for innovative therapeutic strategies to improve outcomes in this serious malignancy.